Enhanced sensitivity of fiber SPR sensor by metal nanoparticle. Issue 3 (31st March 2020) - Liu, Chunlan; Gao, Yang; Gao, YaChen; Wei, Yong; Wu, Ping; Su, Yudong
Abstract : Purpose: This paper aims to clarify the relationship between the performance of the metal nanoparticles and the sensitivity of the fiber surface plasma resonance (SPR) sensor. It proposes modeling the sensing effects of a single-mode fiber SPR sensor with a cone angle structure decorated with metal nanoparticles. This study uses the metal nanoparticles to the realize enhanced sensitivity of refractive index sensing. Design/methodology/approach: This paper opted for an exploratory study using a simulation approach of finite-difference time-domain (FDTD). Specifically, the effect of size, the material and the shape of the metal nanoparticle on sensing performance are investigated theoretically. Findings: In conclusion, it is evident that the localized SPR (LSPR) effect weakens as the diameter of the gold nanosphere increases, the SPR effect enhances and the SPR sensitivity increases first and then decreases. The metal nanoparticle with the different materials and different shapes also have different LSPR and SPR sensitivity and wavelength length dynamic range. The investigation shows that, by changing parameters, the reflection spectra of the fiber SPR sensor exhibit an obvious transition from LSPR to SPR characteristics, and enhanced sensitivity of the refractive index is realized. Originality/value: This paper fulfills an identified need to study how the sensitivity of the fiber SPR sensor can be enhanced by the metal nanoparticle. After the optimization of parameters, the sensitivity of 5, 140 nm/RIU is achieved, which provides a new research direction for sensitivity enhancement of fiber SPR sensor.